Tutorial Programme Workshop: Capacitating tutors on facilitation skills relevant for tutorial sessions, tutors’ Reflections, experiences and Professional Development Workshop needs at the Faculty of Management and Administration Sciences (FMPAS) at Walter - Makala, Qonda; Pangwa, Nocwaka; Asoba, Samson Nambei (Journal of Ecohumanism, 2025)
This study explores tutors’ perceptions and experiences regarding a professional development workshop held on 14 May 2025 in the Faculty of Management and Administration Sciences (FMPAS). The research sought to understand tutors’ reflections on the workshop’s effectiveness, their developmental needs, and suggestions for improving similar interventions. A qualitative approach was adopted, drawing data from reflective responses provided by 48 tutors. Thematic analysis revealed strong appreciation for the training’s relevance and delivery, while also highlighting areas for improvement, including more structured mentorship and technological upskilling. Recommendations include developing continuous support structures, tailoring content to diverse experience levels, and fostering communities of practice. These insights can guide institutions in designing responsive capacity-building initiatives that support tutors’ professional growth.